Religious Moderation Implementation in Islamic Education: A Systematic Review - Musyahid, Musyahid (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Islamic education is significant in confronting the growing threats of religious radicalism and extremism that jeopardize global stability. This systematic study aims to determine how religious moderation is practiced within Islamic education. Following the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines, this research systematically explores two significant databases, Google Scholar and Scopus. The initial search is centred on titles and keywords associated with applying religious moderation within the scope of Islamic education, spanning 2019 to 2023. Approximately 1,060 pertinent publications have been pinpointed in the preliminary search results. After implementing a set of criteria for selection, 16 articles have been chosen for further scrutiny. The research findings revealed that the execution of religious moderation manifests through diverse channels, such as school initiatives, the introduction of moderation values to newcomers, integration into the curriculum, the subtler facets of the curriculum, ceremonial and national events, and the utilization of lecture-style sessions and interactive Q&A approaches. Simultaneously, reinforcing religious moderation is actualized through the cultivation of advanced critical thinking, the moulding of moderate character, the mitigation of radicalism, the integration of moderation principles into real-world scenarios, the pivotal roles of educators and educational institutions, and the adoption of successful models.